Sources, Pathways, and Drivers of Sub‐Antarctic Mode Water Formation - Bieito Fernández Castro; Alberto C. Naveira Garabato; Matthew Mazloff; Richard G. Williams (AGU Advances)
Abstract Sub‐Antarctic Mode Waters (SAMWs) form to the north of the Antarctic Circumpolar Current in the Indo‐Pacific Ocean, whence they ventilate the ocean's lower pycnocline and play an important role in the climate system. With a backward Lagrangian particle‐tracking experiment in a data‐assimilative model of the Southern Ocean (B‐SOSE), we address the long‐standing question of the extent to which SAMWs originate from densification of southward‐flowing subtropical waters versus lightening of northward‐flowing Antarctic waters sourced by Circumpolar Deep Water (CDW) upwelling. Our analysis evidences the co‐occurrence of both sources in all SAMW formation areas, and strong inter‐basin contrasts in their relative contributions. Subtropical waters are the main precursor of Indian Ocean SAMWs (70%–75% of particles) but contribute a smaller amount (<40% of particles) to Pacific SAMWs, which are mainly sourced from the upwelled CDW. By tracking property changes along particle trajectories, we show that SAMW formation from northern and southern sources involves contrasting drivers: subtropical source waters are cooled and densified by surface heat fluxes, and freshened by ocean mixing. Southern source waters are warmed and lightened by surface heat and freshwater fluxes, and they are made either saltier by mixing in the case of Indian SAMWs, or fresher by surface fluxes in the case of Pacific SAMWs. Our results underscore the distinct climatic impact of Indian and Pacific SAMWs formation, involving net release of atmospheric heat and uptake of atmospheric freshwater, respectively; a role that is conferred by the relative contributions of subtropical and Antarctic sources to their formation.